2022
DOI: 10.31635/ccschem.021.202100910
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastable π–π Stacked Porous Organic Molecular Framework as a Crystalline Sponge for Rapid Molecular Structure Determination

Abstract: The crystalline sponge method is a pragmatic and promising strategy for molecular structure determination.However, the dominant metal-organic framework crystal sponge platforms are always facing poor chemical stability, especially solvent instability, which has hampered their application in vaster domain. Herein we report an ultra-stable π-π stacked porous organic molecular framework which exhibits permanent porosity, high thermal stability, and good chemical resistance. It can efficiently implement an approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…1 However, spectroscopic methods have some limitations. A major disadvantage of NMR spectroscopy has been its low sensitivity and narrow spectrum (0-10 ppm for 1 H-NMR and 0-200 ppm for 13 C-NMR); MS provided information about molecular weight and fragment ions, and IR and UV can only give a rough idea about the functional groups in the molecules. Furthermore, spectroscopic methods only suggest speculative molecular structures that are sometimes incorrect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, spectroscopic methods have some limitations. A major disadvantage of NMR spectroscopy has been its low sensitivity and narrow spectrum (0-10 ppm for 1 H-NMR and 0-200 ppm for 13 C-NMR); MS provided information about molecular weight and fragment ions, and IR and UV can only give a rough idea about the functional groups in the molecules. Furthermore, spectroscopic methods only suggest speculative molecular structures that are sometimes incorrect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al have reported an ultrastable π-π stacked porous organic molecular framework as a "crystalline sponge" to determine guests, but the solvent-accessible volume was only 10.6% and only small volume guests can enter the sponge. 13 (iii) Yaghi et al developed a coordinative alignment of molecules in chiral metal-organic frameworks, 14 in which guest molecules including liquid compounds coordinate with aluminum ions. However, the framework still needs a tedious solvent exchange and activation process.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the luminescence of organic molecules in the aggregated state depends not only on their intrinsic molecular structure, but also on the aggregation types, 61 so the relation between intermolecular stacking and luminescent behavior is clear because precise atom locations may be obtained from single-crystal structure analysis. It facilitates further understanding of the luminescence properties of porous crystals.…”
Section: Luminescent Opcs and Applicationsmentioning
confidence: 99%
“…developed a distinctive noncovalent π⋅⋅⋅π interaction‐stacked organic framework (πOF) with permanent porous and remarkable conductive properties [8] . We employed an organic molecule carrying three identical propeller‐like wedges to construct a durable πOF, which can be used as a new crystalline sponge for rapid molecular structure determination [9] . In general, use of an organic molecule with multiple branches of large π‐conjugate planes to enhance intermolecular π⋅⋅⋅π interactions is a promising strategy to construct stable molecular frameworks.…”
Section: Figurementioning
confidence: 99%